Effect of the Blocking Oxide Layer With Asymmetric Taper Angles in 3-D NAND Flash Memories - Jun Gyu Lee (IEEE Journal of the Electron Devices Society, 2021)
The tapered channel effect is a major concern in three-dimensional (3-D) NAND technology because the effect causes differences in the electrical characteristics, including the threshold voltage (VT), between the upper and the lower cells. We simulated the tapered channel effect by using Sentaurus technology, computer-aided design (TCAD) tools, and based on the results, we propose a novel method to lessen the non-uniformity of the threshold voltage shift ( ${Δ }\text{V}_{ T}$ ) between the cells. The difference in ${Δ }\text{V}_{ T}$ between the upper and the lower cells due to the tapered channel can be reduced by employing a tapered blocking oxide layer with a proper taper angle. These results will be helpful in designing reliable 3-D NAND flash memories.